دراسة إزهار وإثمار موجات النمو الفصلية لصنف البرتقال فالنسيا في ظروف المنطقة الساحلية وتأثيرها على الإنتاجية - ديب علي; الخطيب علي; حامد وضاح (Latakia University Journal -Biological Sciences Series, 2019)
أجريت هذه الدراسة في بستان تابع لقسم بحوث الحمضيات في طرطوس خلال موسمي(2007-2008) على أشجار حمضيات من صنف الفالنسيا المطعمة على أصل النارنج(الزفير)، وهي بطور الإنتاج الكامل (20) سنة, وخلصت النتائج إلى الآتي: - يتركز الإزهار والإنتاج على موجة النمو الخريفية وتفوقت معنوياً على موجتي النمو الصيفية والربيعية. - أظهرت الدراسة ارتفاع نسبة العقد في النمو الزهري الطرفي المنتهي بزهرة واحدة وبفرق معنوي على النمو الزهري المختلط والنورة الزهرية, في حين تفوق النمو الزهري المختلط بكمية الإنتاج وبفرق معنوي على باقي النموات الثمرية. - لم تظهر جهات الشجرة فروقاً معنوية من حيث الإنتاج. This study has been conducted in a field related to Citrus Research Section in Tartos during (2007-2008) seasons on Citrus trees from Valencia variety grafted on Sour Orange rootstock, in produce full stage (20 years), and the results have shown that flowering and producing intensified on autumnal season cycle and morally excessive on both spring and summer season cycles. Moreover, this study has also shown a high fertilize average in leafy- inflorescence that ended with one flower and a morally difference over both mixture (leafy and flowering) and flowering inflorescences, while mixture inflorescence excessive in produce amount morally on other inflorescence types. Sides of trees have not shown any moral difference in produce.